The nexus between money supply and inflation in sri lanka - Kesavarajah, M.; Amirthalingam, K. (University of Jaffna, 2012)
The purpose of this study is to examine the nexus between money supply and inflation in Sri Lanka over the period 1978 to 2010. The annual time series secondary data on inflation, money supply, budget deficit and exchange rate were drawn from various annual reports of Central Bank of Sri Lanka. Moreover, Johanson and Juseliues multivariate cointegration test and Granger causality tests are employed to estimate the long run equilibrium relationship among the variables. The Augmented Dickey Fuller (ADF) unit root test was used to examine the properties of the time series variables and to determine the order of integration for each series in this study. The choice of the lag length of the time series variables are based on the minimum Akaike Information Criterion (AIC). According to the Johansen Maximum likelihood test, the computed trace statistic, maximum Eigen statistic and their corresponding critical statistic indicates that the null hypothesis of “no cointegration” can be rejected at five percent level of significance. This result supports the presence of long run relationship among the variables. Moreover, the Granger causality test indicates while there was a significant causality from money supply to inflation and exchange rate to inflation while the causality from budget deficit to inflation was insignificant. Further, analysis indicates that inflation is mainly attributed to the monetary expansion in Sri Lanka during the post liberalization period. Therefore, this study concludes that money supply variable can be used as an effective policy instrument to maintain the price stability in Sri Lanka.
Keywords: Causality; Exchange rate inflation; Money Supply